State of the Art of Single‐Walled Carbon Nanotube Synthesis on Surfaces. (17th July 2014) - Chen, Yabin; Zhang, Yingying; Hu, Yue; Kang, Lixing; Zhang, Shuchen; Xie, Huanhuan; Liu, Dan; Zhao, Qiuchen; Li, Qingwen; Zhang, Jin
<x xml:space="preserve">Abstract</x> Single‐walled carbon nanotubes (SWNTs) directly synthesized on surfaces are promising building blocks for nanoelectronics. The structures and the arrangement of the SWNTs on surfaces determine the quality and density of the fabricated nanoelectronics, implying the importance of structure controlled growth of SWNTs on surfaces. This review summarizes the recent research status in controlling the orientation, length, density, diameter, metallicity, and chirality of SWNTs directly synthesized on surfaces by chemical vapor deposition, together with a session presenting the characterization method of the chirality of SWNTs. Finally, the remaining major challenges are discussed and future research directions are proposed.